ANALISIS POSTUR KERJA PEKERJA PROSES PENGEASAHAN BATU AKIK DENGAN MENGGUNAKAN METODE REBA - Sulaiman, Fahmi; Sari, Yossi Purnama (Jurnal Optimalisasi, 2015)
Work Station, human Work Factor contains a high hazard potential so we need a preventive effort to prevent accidents and illness due to improper working posture. The purpose of this study was to determine the relationship postures with complaints system muscoloskletal workers agate grinding process so that the system can meminimalisirkan complaint musculoskletal workers agate grinding. To determine the posture disorders occurring in workers then used method of REBA (Rapid EntireBody Asssessment). That is the method used to analyze the workers based on the position of the body. This method is designed to evaluate the work or activities, where such work has a tendency to cause discomfort such as fatigue in the neck, spine, arm. From the observations that have been made are not ergonomic working position. It is necessary for improvement of working methods by the company.Kata Kunci: Work Posture, Work Station, Musculoskeletal, REBA, Gems Stone.